2017
DOI: 10.1063/1.4973743
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of p-type depletion doping for InGaN/GaN-based light-emitting diodes

Abstract: Due to the limitation of the hole injection, p-type doping is essential to improve the performance of InGaN/GaN multiple quantum well light-emitting diodes (LEDs). In this work, we propose and show a depletion-region Mg-doping method. Here we systematically analyze the effectiveness of different Mg-doping profiles ranging from the electron blocking layer to the active region. Numerical computations show that the Mg-doping decreases the valence band barrier for holes and thus enhances the hole transportation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Therefore, it shall be advisible to increase the hole injection efficiency by increasing the hole density for the p-type hole injection layer, which can be obtained by adopting specially designed architectures. It has been suggested that the polarization-induced three-dimensional hole gas (3DHG) that is obtained by grading the Al composition in the AlGaN layer can enable a higher hole concentration. The polarization-induced-doping design numerically proves to be effective in facilitating the hole injection capability for the DUV LED, which has been reported by Chang et al In addition, the hole concentration for the p-type hole injection layer can also be increased by doping the last quantum barrier with Mg dopants, , such that the Mg dopants in Mg-doped last quantum barrier can be more efficiently ionized by the polarization induced electric field, while the built-in electric field can deplete the holes and the holes are finally stored in the p-type hole injection layer. It is reported that the activation energy of Mg dopants for the GaN film can be even lower than 100 meV by adopting the Mg–In codoping technology, by means of which the hole concentration can be increased to the order of 10 18 cm –3 . , Besides increasing the hole concentration for the p-type hole injection layer, another approach to boost the hole injection into the quantum well region is to energize holes, which is very helpful to facilitate the thermionic emission for holes to cross over the p-type electron blocking layer (p-EBL).…”
mentioning
confidence: 94%
“…Therefore, it shall be advisible to increase the hole injection efficiency by increasing the hole density for the p-type hole injection layer, which can be obtained by adopting specially designed architectures. It has been suggested that the polarization-induced three-dimensional hole gas (3DHG) that is obtained by grading the Al composition in the AlGaN layer can enable a higher hole concentration. The polarization-induced-doping design numerically proves to be effective in facilitating the hole injection capability for the DUV LED, which has been reported by Chang et al In addition, the hole concentration for the p-type hole injection layer can also be increased by doping the last quantum barrier with Mg dopants, , such that the Mg dopants in Mg-doped last quantum barrier can be more efficiently ionized by the polarization induced electric field, while the built-in electric field can deplete the holes and the holes are finally stored in the p-type hole injection layer. It is reported that the activation energy of Mg dopants for the GaN film can be even lower than 100 meV by adopting the Mg–In codoping technology, by means of which the hole concentration can be increased to the order of 10 18 cm –3 . , Besides increasing the hole concentration for the p-type hole injection layer, another approach to boost the hole injection into the quantum well region is to energize holes, which is very helpful to facilitate the thermionic emission for holes to cross over the p-type electron blocking layer (p-EBL).…”
mentioning
confidence: 94%
“…Zinc-blende is hoped to be more amenable to doping than the wurtzite GaN [ 15 , 16 ]. Most of the previous studies focused on the effect of surface adsorption [ 17 , 18 , 19 , 20 ], defects [ 21 , 22 , 23 ] and doping [ 24 , 25 , 26 , 27 ] on the chemical adsorption performance and their effect on electronic and optoelectronic properties of wurtzite GaN. Li et al [ 28 ] pointed out that the density of states around the Fermi level for the wurtzite structure are much lower than that for the zinc-blende structure, which results in a wider band gap.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulations, the Auger recombination coefficient was set to 1 × 1,042 m 6 /s and 40% of the polarization charges were assumed such that 60% of the theoretical polarization charges were released because of the crystal strain relaxation by generating dislocations. The other parameters used in the simulation can be found elsewhere (Meneghini et al, 2009;Kim et al, 2010;Kuo et al, 2011;Park et al, 2013;Zhang et al, 2013;Zhang et al, 2017).…”
Section: Methodsmentioning
confidence: 99%